2016
DOI: 10.5005/jp-journals-10024-1800
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Coconut Oil pulling on Streptococcus mutans Count in Saliva in Comparison with Chlorhexidine Mouthwash

Abstract: Edible oil-pulling therapy is natural, safe and has no side effects. Hence, it can be considered as a preventive therapy at home to maintain oral hygiene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 15 publications
3
35
0
3
Order By: Relevance
“…The lauric acid content of coconut oil can easily react with saliva, which is alkalic, and form lauric sodium, the main content of soap; this accounts for the cleaning action and decrease in plaque accumulation [3,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…The lauric acid content of coconut oil can easily react with saliva, which is alkalic, and form lauric sodium, the main content of soap; this accounts for the cleaning action and decrease in plaque accumulation [3,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been done on oil pulling and the results showed proves that the method is able to prevent many oral conditions by combating microbial growth in the mouth environment. In a study conducted [18], VCO used in oil pulling had reduced 22.79% colony growth of Streptococcus mutans (S. mutans) while chlorohexidine showed 25.72% reduction of colonial growth. Among few studies conducted on coconut oil, sunflower oil, sesame oil, and other edible oils against chlorhexidine, results showed that oil pulling is able to reduce halitosis and reduce the bacteria count which causes it to drop to a significant amount, reducing gingivitis and plaque as effectively as chlorhexidine [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted [18], VCO used in oil pulling had reduced 22.79% colony growth of Streptococcus mutans (S. mutans) while chlorohexidine showed 25.72% reduction of colonial growth. Among few studies conducted on coconut oil, sunflower oil, sesame oil, and other edible oils against chlorhexidine, results showed that oil pulling is able to reduce halitosis and reduce the bacteria count which causes it to drop to a significant amount, reducing gingivitis and plaque as effectively as chlorhexidine [18][19][20][21]. Furthermore, oil pulling has advantages over chlorhexidine that oil pulling does not leaves staining, no lingering aftertaste, and most importantly no allergy [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations